The Influence of Work Motivation, Work Discipline, and Work Environment on Employee Performance at Bank Mandiri Taspen - Sasthiya Ardania Girsang; Melkyory Andronicus; Desmin Christmas Zalukhu; Munawarah Munawarah (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
This study aims to analyze the effect of Work Motivation, Work Discipline, and Work Environment on Employee Performance at Bank Mandiri Taspen Medan, both partially and simultaneously. This study used a quantitative approach with a causal associative research design. The population as well as the sample consisted of all 30 employees of Bank Mandiri Taspen Medan, using a saturated sampling technique (census). Data were collected through questionnaires and analyzed using multiple linear regression analysis with the assistance of SPSS version 26. The partial test results showed that Work Motivation had a positive and significant effect on Employee Performance (t-count = 2.522; sig. = 0.018), Work Discipline had a positive and significant effect on Employee Performance as the most dominant variable (t-count = 3.293; sig. = 0.003), and Work Environment had a positive and significant effect on Employee Performance (t-count = 2.361; sig. = 0.026). Simultaneously, these three variables had a significant effect on Employee Performance (F-count = 102.393; sig. = 0.000) with an Adjusted R² value of 0.913, indicating that the three variables were able to explain 91.3% of the variation in Employee Performance. The regression equation obtained was: Y = -0.776 + 0.361X₁ + 0.426X₂ + 0.238X₃. This study concludes that improving motivation, strengthening discipline, and creating a conducive work environment are strategic keys to improving employee performance at Bank Mandiri Taspen Medan.